PENGARUH OPPORTUNISTIC BEHAVIOUR, MONITORING MECHANISM DAN FINANCIAL DISTRESS TERHADAP EARNINGS MANAGEMENT - Wynne Nathanael; Elfina Astrella Sambuaga (Universitas Pelita Harapan, 2021)
This study aims to test the opportunistic behavior, monitoring mechanism and financial distress on earnings management in non-financial companies listed on the Indonesia Stock Exchange (BEI) for the period 2010-2019. The sampling technique used was purposive sampling method. Earnings management can be influenced by various factors, such as profitability,free cash flow,leverage and financial distress.The independent variables to be tested in this study are return on assets, free cashflow,debt ratio and financial distress as measured by the Altman Z-Score.Earnings management as the dependent variable will be measured the value ot its discretionary accruals using the Kothari modal. The research will be regressed with multiple linear regression using SPSS (version 25). The result showed that opportunistic behaviour had a significant positive effect only when measured by the cash flow. Monitoring mechanism as measured by leverage and financial distress has a significance positive effect on earnings management